Integrating Language Communication and Islamic Literacy: The Spiral Andromeda Philosophy for Adapting Curriculum at Supra, Macro, Meso, and Micro Levels - Awliya Dara Fitriadi; Aisyah Karlina; Anisa Faizah Avrilia; Annisa Rahmadira; Kalayo Hasibuan (Journal of Applied Linguistics, 2026)
This article explores the intricate relationship between language communication and Islamic literacy through the lens of the Spiral Andromeda Philosophy. It aims to adapt and develop curriculum levels supra, macro, meso, and micro focusing on classroom practices. Utilizing a qualitative approach, this study analyzes existing literature and curriculum frameworks. The findings suggested that integrating Islamic literacy into language communication enhances students' understanding and application of both languageand Islamic values. This integration is essential for developing a holistic educational framework that aligns with the principles of the Merdeka Curriculum. Recommendations for curriculum developers and educators are provided to facilitate this integration effectively. Keywords : Language Communication, Islamic Literacy